The prince : With related documents - Machiavelli, Niccolò; Connell, William J. (Boston Bedford/St. Martin's, 2005)
In his lucid introductory essay, William J. Connell offers fresh insights into Machiavelli's life, the meaning of his work, the context in which it was written, and its influence over time.
Includes bibliographical references (p. 195-198) and index
Keywords: Tham khảo